Menyelami Kedalaman Tasawuf: Pendekatan Kompleks Sebagai Agenda - Ahmad Syatori, Syatori (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
The presence of Sufism in the midst of this global society is not only to provide responses and answers, not only question religious problems, but also about social, political and economic conditions of mankind. Sufism is an Islamic oasis that has a mandate in delivering necessary of human spirituality to the perfect stage. Sufism study is an Islamic study born from the womb of Sufism treasures in depth. Sufis have always rested on the dualism of truth between innate and inward, between historical and trans-historical sociology. Spiritual experimentation is not merely an individualistic idealistic experimentation, but also a social-idealistic experiment driven by a real sociological situation according civilization of the times. Then, to maximize the results of good and correct Sufism studies, it should use all existing methodologies inseparably. This is typical as a multidisciplinary approach. Use one of methodology without the other will reduce the formulation of Sufism which actually built on the spiritual experience of each individual original Sufi figure, the struggle of faith and their passion when struggling with the social reality faced and the recognition of the central text of Islam, namely Qur'an and hadith as normative foundation. Thus a brief review of discussion Sufism which provides an image complexity of approaches and instruments in reading it, with various aspects and scopes.